2019
DOI: 10.1088/1748-9326/aafd4e
|View full text |Cite
|
Sign up to set email alerts
|

Recent global warming as confirmed by AIRS

Abstract: This paper presents Atmospheric Infra-Red Sounder (AIRS) surface skin temperature anomalies for the period 2003 through 2017, and compares them to station-based analyses of surface air temperature anomalies (principally the Goddard Institute for Space Studies Surface Temperature Analysis (GISTEMP)). The AIRS instrument flies on EOS Aqua, which was launched in 2002 and became stable in September 2002. AIRS surface temperatures are completely satellite-based and are totally independent of any surface-based measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 31 publications
2
61
0
Order By: Relevance
“…Sampling bias: Recent studies have shown the likely presence of bias in surface temperature products compared to the true global mean (Cowtan & Way, 2014;Jones, 2016;Karl et al, 2015;Simmons et al, 2010Simmons et al, , 2016. In addition, recent evidence from remote sensed temperature analyses suggest that production GIS-TEMP may be underestimating Arctic warming (Susskind et al, 2019). To quantify the potential sampling 10.1029/2018JD029522 biases due to limited station coverage, we introduce a potential systematic additive bias k and multiplicative bias k .…”
Section: Lsat Sampling Extensionsmentioning
confidence: 99%
“…Sampling bias: Recent studies have shown the likely presence of bias in surface temperature products compared to the true global mean (Cowtan & Way, 2014;Jones, 2016;Karl et al, 2015;Simmons et al, 2010Simmons et al, , 2016. In addition, recent evidence from remote sensed temperature analyses suggest that production GIS-TEMP may be underestimating Arctic warming (Susskind et al, 2019). To quantify the potential sampling 10.1029/2018JD029522 biases due to limited station coverage, we introduce a potential systematic additive bias k and multiplicative bias k .…”
Section: Lsat Sampling Extensionsmentioning
confidence: 99%
“…For instance, AIRS monthly temperature and humidity profile products have been published as one of many Observations for Model Intercomparison Projects (Obs4MIPs) datasets (Tian et al 2013a(Tian et al , 2019 and they have been widely used in the climate model evaluation for the phase 5 of the Coupled Model Intercomparison Project (CMIP5) (Tian et al 2013a;Tian 2015). Susskind et al (2019) found that recently observed global warming was confirmed by AIRS data.…”
Section: Abo Versus Abd Averaging For Airs Monthly Productmentioning
confidence: 99%
“…The GES DISC, in collaboration with the NASA Sounder Team at the Jet Propulsion Laboratory (JPL), released the AIRS product from the version 6 algorithm in early 2013. The version 6 algorithm represents a significant improvement over previous versions with greater stability, yield, and quality of data products (Susskind et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Southern Oscillations responsible for El Niño events have occurred for at least 130 000 years (Tudhop et al 2001) suggesting ample opportunity for natural selection to enhance the capability of trees to tolerate irregular drought events (Harrison 2000, Detto et al 2018. However, climate change is increasing the severity and frequency of El Niño events (Breshears et al 2005, Allen et al 2010, Thirumalai et al 2017, Freund et al 2019; and higher than average temperatures recorded across Southeast Asia in 2015 and early 2016 were attributed to a climate-change amplified El Niño event (Thirumalai et al 2017, Susskind et al 2019. Higher temperatures increase evaporative demand and therefore exacerbate the severity of drought events (Adams et al 2009).…”
Section: Introductionmentioning
confidence: 99%